2011
DOI: 10.1159/000328510
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Motives in Clinical and General Populations

Abstract: Aims: This paper had three aims: (1) to validate a Spanish adaptation of the Modified Drinking Motives Questionnaire-Revised (M DMQ-R), (2) to explore the relationship of each drinking motive with different patterns of alcohol use, and (3) to compare the drinking motives of moderate drinkers, heavy drinkers, and alcohol abusing/dependent individuals. Methods: Two studies were carried out. In Study 1, a sample of 488 participants completed the M DMQ-R and a self-report scale of alcohol consumption in order to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
52
0
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 94 publications
12
52
0
21
Order By: Relevance
“…Indeed, endorsement of the coping motives in our sample was consistent with other normative, undergraduate samples (Grant et al, 2007) and significantly lower than clinical samples (Mezquita et al, 2011). Perhaps the coping motive would be a significant moderator of outcomes in a more heavy-using, clinical sample.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, endorsement of the coping motives in our sample was consistent with other normative, undergraduate samples (Grant et al, 2007) and significantly lower than clinical samples (Mezquita et al, 2011). Perhaps the coping motive would be a significant moderator of outcomes in a more heavy-using, clinical sample.…”
Section: Discussionsupporting
confidence: 88%
“…y evitar ciertas situaciones, como sentirse excluido del grupo o presionado por los amigos. El logro de refuerzo positivo -tanto de naturaleza social como emocional-es también una de las principales motivaciones asociadas al consumo abusivo de alcohol (Abbey, Smith y Scott, 1993;Kuntsche y Cooper, 2010;Mezquita et al, 2011) y a la participación de los universitarios en botellones (Gó-mez-Fraguela et al, 2008). Asimismo, los posibles beneficios asociados a la conducta son también buenos predictores de las conductas arriesgadas de los adolescentes (Parsons et al, 2000;Rolison y Scherman, 2003).…”
Section: Discussionunclassified
“…Only in the past few years have studies in a range of more diverse countries such as Great Britain (Atwell et al, 2011;Bruce et al, 2012), Germany (Wurdak et al, 2010), Hungary (Németh et al, 2011a;Urbán et al, 2008), Italy (Graziano et al, 2010;Mazzardis et al, 2010), the Netherlands (Crutzen and Kuntsche, 2013;SchellemanOffermans et al, 2011), Spain (Mezquita et al, 2011;Németh et al, 2011b), and Sweden (Comasco et al, 2010) investigated the structure of drinking motives and/or their links to alcohol-related outcomes. The evidence from these studies and from previous research is fairly consistent in that adolescents reported that they drank most often for social motives, followed by enhancement, coping, and conformity motives in that order (Cooper, 1994;Kuntsche and Kuntsche, 2009;Kuntsche et al, 2008).…”
mentioning
confidence: 99%